Governança e coordenação : a função do porto de Paranaguá enquanto influenciador na dinâmica operacional e competitiva na cadeia agroindustrial da soja - Silva, Marcos Cipriano da (2006)
Possible implications and development of governance and coordination are evaluated, which involving the Port of Paranaguá as a leading firm within the operational and competitive agro-industrial chain for soybean export in the state of Paraná, Brazil. The methodology of this qualitative research was chiefly foregrounded in case studies and content analyses. Results show that the leading firm entitled Port of Paranaguá directly affected operational and competitive dynamics when it established standards and sanctions in the soybean agro- industrial chain, especially with regard to the quality of and the issues on transgenic products. This fact has been highlighted by governance activities on norms and regulations through authority reinforcement. The Port of Paranaguá developed diminished activities with regard to coordination when it obtained the adherence of agents belonging to its framework.